2014
DOI: 10.1111/jgh.12513
|View full text |Cite
|
Sign up to set email alerts
|

Association of cannabinoid type 1 receptor and fatty acid amide hydrolase genetic polymorphisms in Chinese patients with irritable bowel syndrome

Abstract: The variation in the (AAT)n repeat of the CNR1 gene conferred an increased risk for developing IBS, while rs324420 (C385) in the FAAH gene was not associated with IBS pathogenesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
13
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 43 publications
2
13
0
Order By: Relevance
“…In line with a possible role of CNR1 variants in the development of IBS symptoms, allele frequencies of AAT triplet repeats in CNR1 were observed to be associated with IBS in a study of a Korean population . Similar results, namely the detection of eight CNR1 alleles with AAT triplet repeats, were reported in a Chinese IBS cohort, whereas no association could be detected between C385A FAAH polymorphism and IBS pathogenesis . Interestingly, FAAH activity was recently determined in whole colon samples from patients who underwent colectomy for slow transit constipation …”
Section: Cannabinoids and Functional Bowel Disorderssupporting
confidence: 52%
See 1 more Smart Citation
“…In line with a possible role of CNR1 variants in the development of IBS symptoms, allele frequencies of AAT triplet repeats in CNR1 were observed to be associated with IBS in a study of a Korean population . Similar results, namely the detection of eight CNR1 alleles with AAT triplet repeats, were reported in a Chinese IBS cohort, whereas no association could be detected between C385A FAAH polymorphism and IBS pathogenesis . Interestingly, FAAH activity was recently determined in whole colon samples from patients who underwent colectomy for slow transit constipation …”
Section: Cannabinoids and Functional Bowel Disorderssupporting
confidence: 52%
“…69 Similar results, namely the detection of eight CNR1 alleles with AAT triplet repeats, were reported in a Chinese IBS cohort, whereas no association could be detected between C385A FAAH polymorphism and IBS pathogenesis. 70 Interestingly, FAAH activity was recently determined in whole colon samples from patients who underwent colectomy for slow transit constipation. 71 The results revealed a strong decrease in activity in these patients as compared to individuals free of transit dysfunction.…”
Section: Ibs: Genetic Variations and The Ecsmentioning
confidence: 99%
“…5 Camilleri 5 discovered that SERT was lowly expressed in the local intestinal tract of IBS-D patients, which resulted in elevated intestinal 5-HT levels and correlated with IBS-D susceptibility. 5 Cannabinoid receptor 1 (CNR1) is associated with symptom phenotype, pain perception, inhibition of nerve transmission, and colonic transit in IBS-D. 6 Inhibition of CNR1 expression may enhance visceral sensitivity and susceptibility to ulcerative colitis. 7 Furthermore, CNR1 inhibits GI motility in the enteric nervous system, mainly by inhibiting contractile neurotransmitter release.…”
Section: Introductionmentioning
confidence: 99%
“…6,7 Recent studies on the familial aggregation of patients with FGID have indicated that hereditary factors may contribute to susceptibility to FGID. 6,8,9 MicroRNAs (miRNAs) are a class of small noncoding RNAs that regulate gene expression by binding to the 3′-untranslated region (3′-UTR) of the messenger RNA (mRNA) of the target gene. 10 MicroRNAs are involved in the pathogenesis of FGID.…”
Section: Introductionmentioning
confidence: 99%